Prediction of noise from wind turbines: A theoretical and experimental study (2019)
Several noise propagation models used to calculate the noise produced by wind turbines have been reported. However, these models do not accurately predict sound pressure levels. Most of them have been developed to estimate the noise produced by industries, in which wind speeds are less than 5 m/s, and conditions favor its spread. To date, very few models can be applied to evaluate the propagation of sound from wind turbines and most of these yield inaccurate results. This study presents a comparison between noise levels that were estimated using the prediction method established in ISO 9613 Part 2 and measured levels of noise from wind turbines that are part of a wind farm currently in operation. Differences of up to 56.5 dBZ, with a median of 29.6 dBZ, were found between the estimated sound pressure levels and measured levels. The residual sound pressure levels given by standard ISO 9613 Part 2 for the wind turbines is larger for high frequencies than those for low frequencies. When the wide band equivalent continuous sound pressure level is expressed in dBA, the residual varies between -4.4 dBA and 37.7 dBA, with a median of 20.5 dBA. © 2019 Revista Facultad de Ingenieria.Hay muchos modelos de propagación de ruido que se utilizan para calcular el ruido proveniente de los aerogeneradores. Sin embargo, fallan en la precisión con que pueden predecir los niveles de presión sonora. La mayoría de estos modelos han sido desarrollados para estimar el ruido proveniente de las industrias, con velocidades del viento inferiores a 5 m/s y condiciones favorables a su propagación. Hasta ahora hay muy pocos modelos que se puedan aplicar para la propagación del sonido proveniente de los aerogeneradores y la mayoría de ellos arrojan resultados poco precisos. En este artículo se presenta una comparación entre los niveles de ruido estimados a través del método de predicción establecido en la norma ISO 9613 Parte 2 y los niveles de ruido medidos proveniente de los aerogeneradores instalados en un parque eólico en funcionamiento. Se encontraron diferencias entre los niveles de presión sonora estimados y medidos de hasta 56.5 dBZ, con una mediana de 29.6 dBZ. El nivel de presión sonora residual arrojado por la norma ISO 9613 Parte 2 para los aerogeneradores es mayor para las frecuencias altas que para las frecuencias bajas. © 2019 Revista Facultad de Ingenieria.